The orphan nuclear hormone receptor ERRβ controls rod photoreceptor survival - Onishi, Akishi (National Academy of Sciences, 2010)
Mutation of rod photoreceptor-enriched transcription factors is a major cause of inherited blindness. We identified the orphan nuclear hormone receptor estrogen-related receptor β (ERRβ) as selectively expressed in rod photoreceptors. Overexpression of ERRβ induces expression of rod-specific genes in retinas of wild-type as well as Nrl(−/−) mice, which lack rod photoreceptors. Mutation of ERRβ results in dysfunction and degeneration of rods, whereas inverse agonists of ERRβ trigger rapid rod degeneration, which is rescued by constitutively active mutants of ERRβ. ERRβ coordinates expression of multiple genes that are rate-limiting regulators of ATP generation and consumption in photoreceptors. Furthermore, enhancing ERRβ activity rescues photoreceptor defects that result from loss of the photoreceptor-specific transcription factor Crx. Our findings demonstrate that ERRβ is a critical regulator of rod photoreceptor function and survival, and suggest that ERRβ agonists may be useful in the treatment of certain retinal dystrophies.